POSSIBLE USES OF COMPUTER SYSTEMS IN UNIVERSITY TRAINING OF IT PROFESSIONALS - Prokofjeva, Natalija; Zagulova, Diana; Katalnikova, Sabina; Synytsya, Kateryna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
In this paper, learning and knowledge control systems developed by the Faculty of Computer Science and Information Technology of the Riga Technical University are described. These systems are used in teaching various subjects on different study programs and specialties. The paper also presents results of use of computer systems in student self-study and self-control. Students could freely choose, whether or not to use these systems during their studies. We focused on two scenarios of non-compulsory use of computer systems, namely with a motivating system or without one. In both cases students actively used computer systems for self-control and self-study. Our research shows that using computer systems for both knowledge control and study (as opposed to knowledge control alone) increased knowledge level of all students, regardless of their overall performance.